Gene variance in the nicotinic receptor cluster (CHRNA5‐CHRNA3‐CHRNB4) predicts death from cardiopulmonary disease and cancer in smokers. (22nd December 2015) - Halldén, S.; Sjögren, M.; Hedblad, B.; Engström, G.; Hamrefors, V.; Manjer, J.; Melander, O.
Abstract: Background: Genetic variation in the cluster on chromosome 15, encoding the nicotinic acetylcholine receptor subunits ( CHRNA5‐CHRNA3‐CHRNB4 ), has shown strong associations with tobacco consumption and an additional risk increase in smoking‐related diseases such as chronic obstructive pulmonary disease (COPD), peripheral artery disease and lung cancer. Objectives: To test whether rs1051730 (C/T), a tag for multiple variants in the CHRNA5‐CHRNA3‐CHRNB3 cluster, is associated with a change in risk of smoking‐related mortality and morbidity in the Malmö Diet and Cancer study, a population‐based prospective cohort study. Methods: At baseline participants were classified as current ( n = 6951), previous ( n = 8426) or never ( n = 9417) smokers. Cox‐proportional hazards models were used to determine the correlation between rs1051730 and incidence of first COPD, tobacco‐related cancer, other cancer and cardiovascular disease (CVD), and total mortality due to these causes, during approximately 14 years of follow‐up. Results: Amongst current smokers there were 480 first incident COPD events, 852 tobacco‐related cancers, 810 other cancers and 1022 CVD events. A total of 1508 deaths occurred, including 500 due to CVD, 102 due to respiratory diseases and 677 due to cancer. In adjusted additive models, an increasing number of T alleles were associated with a gradual increase in total mortality, incident COPD and tobacco‐related cancer, even after adjustment for smoking quantity. No significant associations were observed amongst never smokers. Conclusion: Our data suggest that gene variance in the CHRNA5‐CHRNA3‐CHRNB4 cluster is associated with an increased risk of death, incidence of COPD and tobacco‐related cancer in smokers. These findings indicate an individual susceptibility to tobacco use and its complications; this may be important when targeting and designing smoking cessation therapies.